2020
DOI: 10.2147/jmdh.s236488
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Rural Pharmacy Practice Landscape: Challenges and Motivators</p>

Abstract: Background: Health outcome delivery for rural and remote Australian communities is challenged by the maldistribution of the pharmacy workforce. High staff turnover rates, reduced pharmacist numbers, and reliance on temporary staff have placed great strain on both state health services and rural community pharmacies. However, recent changes to the demographic profile of the rural pharmacist including a lower average age and increased time spent in rural practice highlights a more positive future for the deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Of the included 13 studies (Table 4 ), eight (62 %) focused on pharmacists only or reported on recruitment and retention factors associated with practicing rurally among health professionals generally. The latter studies, which provided separate data specifically for pharmacists, included one study from Canada [ 33 ] and seven studies from Australia [ 6 , 15 , 35 – 37 , 39 , 40 ]. There were two studies reporting factors for final year pharmacy students and recent graduates, with one from New Zealand [ 34 ] and the other from Canada [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included 13 studies (Table 4 ), eight (62 %) focused on pharmacists only or reported on recruitment and retention factors associated with practicing rurally among health professionals generally. The latter studies, which provided separate data specifically for pharmacists, included one study from Canada [ 33 ] and seven studies from Australia [ 6 , 15 , 35 – 37 , 39 , 40 ]. There were two studies reporting factors for final year pharmacy students and recent graduates, with one from New Zealand [ 34 ] and the other from Canada [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, financial support may act as an incentive among those students who are seeking to work rurally. In addition, in the Australian study by Hays et al [ 15 ], a lack of available resources, such as stock control, access to services, logistical delays, was identified as a disincentive to practice rurally amongst qualified pharmacists.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural community pharmacists have been identified as highly skilled health professionals who are ideally placed to address these shortcomings by providing a variety of expanded services, including disease screening and management, vaccinations and health promotion [ 6 ]. For rural pharmacists working in this challenging environment, their role is often poorly defined with ambiguous boundaries to their recognised scope of practice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%